O movimento da Reforma do Ensino Médio no Brasil a partir dos anos de 1980: um estudo à luz da crítica gramsciana - Germano Júnior, Manoel Messias Soares (2024)
The general objective of this research is to analyze the movement of educational reforms in Brazilian high school education from the 1980s onwards, with a particular focus on their impact on the Humanities subjects. The specific objectives are to map and examine the educational reforms related to high school education through the lens of Gramscian critique; to present the central formulations of Gramsci's educational proposal; to contextualize the main concepts of the high school reform movement, envisioning a process of human emancipation. In this scope, we aim to observe the emphasis Gramsci places on the issue of education, refining this theme of comprehensive human formation and considering its implications for a proposal for Brazilian high school education. To this end, a review of Gramsci's theoretical works was conducted, especially his prison writings (1929-1935), with a focus on Notebook 12, which is directly related to educational and intellectual issues. This review is accompanied by studies of Gramsci's interpreters such as Del Roio (2006); Jacomini (2020); Manacorda (1990, 2010); Nosella (2010); and Schlesener (2011). We also refer to the theoretical antecedents of Marx and Engels (2010), who influenced the development of Gramsci's writings, as well as authors more closely related to the history of Brazilian education such as Kuenzer (2017); Lemos (2016); Maia Filho (2004); Motta and Frigotto (2017); Ramos (2014); and Romanelli (2001). Gramsci proposes an educational model that goes beyond the dual education advocated by bourgeois ideology, seeking to form citizens who are not only professionally capable but also socially and politically aware. He emphasizes the importance of a high school curriculum that reflects the reality of and for the workers, raising their awareness to actively participate in the construction of a school oriented towards their interests. This implies overcoming the current Brazilian high school education and critically analyzing education to combat the fragmented model that serves the demands of capital.